US foreign policy - Cox, Michael 1947-; aStokes, Doug 1972- (Oxford University Press, 2018)
"This new edition reflects the legacy of the Obama administration, the unfurling impacts of President Trump, and the American role in world affairs. It includes new chapters on gender, religion, East Asia, and the Liberal International Order."--Oxford University Press web page, viewed 6/14/18.